Characterization of lipophilic extractives in Acacia mangium wood and pulp - deresination in chemical pulping - Joshi, Lalita; Viljakainen, Esa; Malinen, Raimo O.; Nazhad, Mousa M.; Schmidt-Vogt, Dietrich; Finland (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
Although Acacia mangium is evolving as a typical pulp wood plantation tree in tropical areas, pitch problems associated with it remains as a drawback. Characterization of wood and pulp extractives and finding the means of deresination are the main objectives of this research study. Acacia mangium from a plantation of Thailand was used for this study. All the studies were carried out in laboratory scale. Characterization of extractives of wood and pulp were carried out qualitatively and quantitatively by extraction process followed by gas chromatography with mass spectrometry (GC-MS) and gas chromatography (GC) with flame ionization detector (FID). Deresination by the use of surfactants and additives in cooking and washing, by the removal of fines, by using surfactants in low consistency washing and different stages of bleaching were carried out in the study. Surfactants and additives as tall oil rosin and gum rosin were used in cooking and washing. Hot water washing (70 oC) was carried out in four steps at 10% consistency and washed pulps were analysed for extractives content. To assess the dispersion of extractives and the effect of surfactants at lower consistency, unwashed pulp at 2% consistency was allowed to react with surfactants with the charge of 10 kg/ ton pulp for 5 min. The liquors separated by centrifuging were then analysed for resin content by extraction and GC. A Dynamic Drainage Jar (DDJ) was used to separate fines from the cooked pulp. The pulps with different amount of fines were analysed for resin content by GC. Deresination in different bleaching stages was studied by subjecting the reference pulp to the bleaching sequences of D0-E-D1, D0-Ep-D1, D0-Eop-D1, D0-Eop-Q-PO, D0-Q-PO and Z-Eop. Oxygen de-lignification was carried out prior to these bleaching sequences. The use of surfactants in cooking only, washing only and in cooking followed by washing gave in average a removal of the long-chain fatty acids by 25, 9 and 33% respectively. Removal of fatty alcohol (C28 OH) was found to be more difficult and was 13% at best. Surfactants were found to be more efficient in dispersing resin components at a lower consistency (2%). About 80% more long-chain fatty acids and about 40% more fatty alcohol (C28 OH) dispersions were found in the study when surfactants were used in lower consistency. By the removal of about 18% of the total fines in the pulp, both the long-chain fatty acids and fatty alcohol (C28 OH) were found to be reduced by about 40%. Among the bleaching sequences studied, sequences with pressurized oxygen and peroxide were found very effective in extractives removal. The sequence of D0-Eop-Q-PO was found to decrease long-chain fatty acids content in pulp by 91% and fatty alcohol (C28 OH) by 96% while the sequence of D0-Q-PO was found to reduce long-chain fatty acids by 91% and fatty alcohol (C28 OH) by 99% when compared with reference pulp.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Technical Science in Pulp and Paper Technology
Thesis (Ph.D.) - Asian Institute of Technology, 2009
Keywords: Acacia; Wood-pulp industry